Application of Case Based Reasoning for Student Recommendations Drop Out (Case Study: Adisutjipto College of Technology) - Agustian, Harliyus (Sekolah Tinggi Teknologi Adisutjipto, 2019)
The data of non-active students is an obstacle in a university because it is counted as a student body, thus affecting the lecturer ratio. For that reason, in order to improve the lecturer ratio, a way is needed in addition to adding lecturers, but also by evaluating the data of students who are not active and active to be filtered back by looking at academic data that is known so that students can continue their studies or should be advised to resign or also drop out . To solve these problems a system model is needed that can recommend students as drop out students and can also provide other recommendations that can be used as evaluations. Case-based reasoning method is used to see new data matching with old data, where active student data to be evaluated will be matched with student data that has been dropped out or received a warning letter, so that it will be used as a new solution. Case-based reasoning methods can help in recommending students to drop out or get a warning letter.